The effect of different dietary ionophores and inclusion levels in the finishing diets of lambs - Price, Melville Maurice (University of the Free State, 2011)
The aim of this study was to evaluate the effects of different ionophore types and inclusion levels in feedlot finisher diets on production performance and carcass characteristics of S.A. Mutton Merino lambs. To address the aim of the study, it was divided in two phases namely: firstly, to evaluate the effect of different ionophores on animal production and carcass characteristics and secondly, to evaluate the effects of different dietary ionophore inclusion levels on the same experimental parameters. During the first study (63 days) 60 lambs (29.7 ± 2.5 kg) were randomly allocated to four treatment groups (n=15/treatment) and further subdivided into five replicates (n=3/replicate). Monensin, lasalocid and salinomycin was included into a commercial high protein concentrate (379 g CP/kg DM) at 16.5, 33.0 or 17.5 mg active ingredient/kg feed, respectively. The fourth treatment, namely the control diet was without any ionophore inclusion. Treatment diets (164 g CP/kg DM; 179 g NDF/kg DM) consisted of this protein concentrate (200 g/kg; containing an ionophore or not), maize meal (650 g/kg) and lucerne hay (150 g/kg) representing the four dietary treatments: control (C: no ionophore inclusion), monensin (M), lasalocid (L) and salinomycin (S). During the second study (42 days) 84 (30.7 ± 2.7 kg) lambs were randomly allocated to seven dietary treatment groups (n=12/treatment) and further subdivided into four replicates (n=3/replicate). Treatment diets of the second study consisted of the same basal diet used during the first study, differing only in respect of ionophore type and inclusion level; representing the control (no ionophore included), monensin low (ML: 11 mg active ingredient/kg feed), monensin medium (MM: 16.5 mg active ingredient/kg feed), monensin high (MH: 22 mg active ingredient/kg feed), salinomycin low (SL: 15 mg active ingredient/kg feed), salinomycin medium (SM: 17.5 mg active ingredient/kg feed) and salinomycin high (SH: 20 mg active ingredient/kg feed) treatments. Generally, neither ionophore type nor inclusion level had an effect (P>0.05) on any of the production performance parameters, as well as carcass characteristics determined in both studies. However, in the first study, salinomycin resulted in the highest (P<0.0001) NDF intake (1000 g/lamb/day), whereas monensin included at 22 mg/kg resulted in the lowest (P<0.01) CP (377 g/animal/day) and ash (83 g/animal/day; P<0.01) intake during the second study. In general, the efficiency of monensin, lasalocid and salinomycin, even at different levels, in sheep finisher diets, seem to be similar and does not affect rumen fermentation in such a way to improve feedlot performance and carcass characteristics of lambs when compared with the control treatments.

Die doel van die studie was om die effek van verskillende ionofoortipes en -insluitingspeile binne afrondingsdiëte op die produksie- en karkaseienskappe van Suid-Afrikaanse Vleismerinolammers te evalueer. Om hierdie doel te bereik was die studie in twee fases opgedeel: eerstens, om die invloed van verskillende ionofore op die produksierespons en karkaseienskappe van die lammers te bepaal, en tweedens, om die die effek van verskillende ionofoorinsluitingspeile op bogenoemde maatstawwe te evalueer. Tydens die eerste produksiestudie (63 dae) was „n totaal van 60 lammers (29.7 ± 2.5 kg) ewekansig ingedeel tussen vier dieetbehandelings (n=15 diere/behandeling), waarna elke behandeling verder onderverdeel is in vyf replikasies (n=3 diere/replikasie). Monensin, lasalocid en salinomycin is elk onderskeidelik vooraf ingesluit in „n kommersiële hoë-proteïen konsentraat (379 g RP/kg DM) teen 16.5, 33.0 en 17.5 mg aktiewe bestanddeel/kg voer. Die vierde behandeling, naamlik die kontrole dieet, was sonder enige ionofoor insluiting. Die rantsoene (164 g RP/kg DM; 179 g NBV/kg DM) het uit hierdie hoë-proteïen konsentraat (200 g/kg; met „n ionofoor ingesluit of nie), mieliemeel (650 g/kg) en lusernhooi (150 g/kg) bestaan wat die vier behandelings verteenwoordig naamlik: kontrole (C: geen ionofoor ingesluit), monensin (M), lasalocid (L) en salinomycin (S). Tydens die tweede studie (42 dae) was „n totaal van 84 lammers (30.7 ± 2.7 kg) ewekansig ingedeel tussen sewe behandelings (n=12 diere/behandeling), waarna elke behandeling verder onderverdeel is in vier replikasies (n=3 diere/replikasie). Die diëte wat tydens die tweede produksiestudie gebruik is, het bestaan uit dieselfde basale dieet as tydens die eerste studie, maar het slegs verskil rakende die ionofoor tipe en dienooreenkomstige insluitingsvlakke: wat die kontrole (C: geen ionofoor ingesluit), monensin laag (ML: 11 mg aktiewe bestanddeel/kg voer), monensin medium (MM: 16.5 mg aktiewe bestanddeel/kg voer), monensin hoog (MH: 22 mg aktiewe bestanddeel/kg voer), salinomycin laag (SL: 15 mg aktiewe bestanddeel/kg voer), salinomycin medium (SM: 17.5 mg aktiewe bestanddeel/kg voer) en salinomycin hoog (SH: 20 mg aktiewe bestanddeel/kg voer) behandelings verteenwoordig. Oor die algemeen, het beide die ionofoor tipe sowel as -insluitingsvlak nie „n effek (P>0.05) op enige van die produksieparameters of karkaseienskappe wat gemeet is tydens beide studies gehad nie. Ongeag die beperkte respons rakende beide ionofoor tipe sowel as –insluitingspeil op produksie –en karkaseienskappe, het lammers van die salinomycin behandeling tydens die eerste studie die hoogste (P<0.0001) NBV-inname gehad (1000 g/lam/dag). Tydens die tweede studie het die MH behandeling (monensin teen 22 mg/kg diet) die laagste (P<0.01) RP-inname (377 g/lam/dag) en as-inname (83 g/lam/dag; P<0.01) gehad. As algemene gevolgtrekking wil dit voorkom of die effektiwiteit van monensin, lasalocid en salinomycin, selfs teen verskillende insluitingsvlakke binne skaapafrondingsdiëte, baie soortgelyk is en nie rumenfermentasie tot so „n mate beïnvloed om die produksierespons en karkaseienskappe van lammers noemenswaardig te verbeter nie.
Dissertation (M.Sc.Agric. (Animal, Wildlife and Grassland Sciences))--University of the Free State, 2011
Keywords: Ionophores; Feed additives; Merino sheep -- Carcasses; Merino sheep -- Feed utilization efficiency; Merino sheep -- Feeding and feeds